Techno-economic and environmental assessment of upgrading alternatives for sludge stabilization in municipal wastewater treatment plants. (20th January 2016) - Tomei, Maria Concetta; Bertanza, Giorgio; Canato, Matteo; Heimersson, Sara; Laera, Giuseppe; Svanström, Magdalena
Abstract: In this work we have performed a feasibility study of two upgrading alternatives for sewage sludge stabilization aimed to the reduction of the produced sludge and to the improvement of its qualitative characteristics with respect to its final destination: agricultural use or incineration. The first upgrading (1) proposes the separated thickening: primary sludge is thickened by gravity while dynamic thickening is applied to secondary sludge. The second upgrading (2) introduces a post-aerobic digestion stage (after the anaerobic one), in addition to separate thickening. Technical-economic and environmental assessments have been performed in comparison to a conventional wastewater treatment plant, which operates with gravity thickening and anaerobic digestion of mixed sludge. In the post-aerobic stage, operated with intermittent aeration, additional volatile solids removal of 45% and nitrification and denitrification efficiencies of 97% and 70%, respectively, were achieved. Both upgrading alternatives gained a positive technical evaluation with the only exceptions of the item " Thermal energy consumption " in upgrading 1 for agricultural reuse, and, to a minor extent, the " Energy available for external recovery " for incineration in both upgrading options. Cost analysis showed that the two upgrading alternatives are generally cheaper than the conventional plant, even if the results are dependent on local conditions, which have to be considered. Results of the environmental assessment showed that the upgrades with incineration perform better than the reference for all impact categories except freshwater eutrophication, with upgrading 2 as the best option. For the agricultural use, different results were obtained for the different impact categories with critical aspects mainly related to phosphorus and ammonia emissions for upgrading 1. Graphical abstract: Highlights: We analysed two upgrading options for enhancing sewage sludge stabilization. We performed techno-economic and environmental assessment of the two options. Intermittent aeration in post-aerobic treatment allowed efficient nitrogen removal. The two proposed upgrading options performed better than the reference plant. Environmental concerns relate to phosphorus and ammonia emissions.